Analisis Pengaruh Kinerja Keuangan terhadap Profitabilitas Bank Syariah di Indonesia - Heri Sudarsono (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2017)
This study aimed to analyze the factors affecting the amount of profitability (ROA) provided by Islamic banking in Indonesia. The data which is used is taken from the financial report of the Shari’a Bank during the 2011-2016 periods by using montly financial statement This study uses a Vector Error Correction Model (VECM) to see the long-term effect and response to shock that occur in the studied variables. The result shows that in the long run, the percentage Financing (FIN) and BOPO give a positive siqnifikant effect on the ROA, while third party funds (DPK), percentage profit and loss sharing (TBH), financial to deposit ratio (FDR) has negative and siqnificant effect on the ROA. Sertifikat Bank Indonesia Syariah (SBIS) and non performing finance (NPF) have no significant effect on the ROA. In short run, ROA give a negatif and siqnificant effect on the ROA and FDR give a positif and siqnificant effect, while DPK, FIN, SBIS, TBH, NPF and BOPO have no sinificant effect on the ROA. Therfore, shocks that occur in the ROA, FIN, FDR , NPF dan BOPO positively responded by ROA and will be stable in the long term. While the shocks that occur in the percentage of FDR, SBIS and TBH responded negatively by financing and will be stable in the long term.Penelitian ini bertujuan untuk menganalisis faktor-faktor yang memengaruhi profitabilitas (ROA) perbankan syariah di Indonesia. Data yang digunakan data bulanan dari laporan keuangan bank syariah periode 2010-2015. Penelitian ini mengunakan Vector Error Correction Model (VECM) untuk melihat dampak jangka panjang dan respon terhadap dampak shock pada setiap variabel terhadap pembiayaan. Hasil olah data menunjukkan bahwa FIN dan BOPO berhubungan positif terhadap ROA, sedangkan DPK, TBH, FDR berhubungan negatif terhadap dan ROA SBIS dan NPF tidak berpengaruh terhadap tingkat ROA. Dalam jangka pendek, ROA berhubungan negatif, tetapi FDR terhadap ROA berhubungan positif. Sedangkan DPK, FIN, SBIS, TBH, NPF and BOPO tidak berhubungan dengan pembiayaan. Di lain pihak, respon pembiayan terhadap goncangan yang terjadi terjadi pada ROA, FIN, FDR, NPF dan BOPO direspon positif oleh ROA. Sedangkan respon ROA terhadap goncangan yang terjadi pada FDR, SBIS dan TBH adalah negatif.